Maternal and fetal outcomes in pregnancies complicated by the inherited aortopathy Loeys–Dietz syndrome. (1st April 2019) - Cauldwell, M; Steer, PJ; Curtis, S; Mohan, AR; Dockree, S; Mackillop, L; Parry, H; Oliver, J; Sterrenburg, M; Bolger, A; Siddiqui, F; Simpson, M; et al.
Abstract : Objective: Pregnancies in women with Loeys–Dietz syndrome (LDS) are rare and are typically documented in case reports only. Early reports suggested high rates of maternal complications during pregnancy and the puerperium, including aortic dissection and uterine rupture, but information on fetal outcomes was very limited. Design: A retrospective cohort study. Setting: Eight specialist UK centres. Sample: Pregnant women with LDS. Methods: Data was collated on cardiac, obstetric, and neonatal outcomes. Main outcome measures: Maternal and perinatal outcomes in pregnancies complicated by LDS. Results: Twenty pregnancies in 13 women with LDS were identified. There was one miscarriage, one termination of pregnancy, and 18 livebirths. In eight women the diagnosis was known prior to pregnancy but only one woman had preconception counselling. In four women the diagnosis was made during pregnancy through positive genotyping, and the other was diagnosed following delivery. Five women had a family history of aortic dissection. There were no aortic dissections in our cohort during pregnancy or postpartum. Obstetric complications were common, including postpartum haemorrhage (33%) and preterm delivery (50%). In all, 14/18 (78%) of deliveries were by elective caesarean section, at a median gestational age at delivery of 37 weeks. Over half the infants (56%) were admitted to the neonatal unit following delivery. Conclusion: Women with LDS require multidisciplinary specialist management throughout pregnancy. Women should be referred for preconception counselling to make informed decisions around pregnancy risk and outcomes. Early elective preterm delivery needs to be balanced against a high infant admission rate to the neonatal unit. Tweetable abstract: Pregnancy outcomes in women with Loeys–Dietz syndrome. Tweetable abstract: Pregnancy outcomes in women with Loeys–Dietz syndrome.